2019
DOI: 10.1021/acsaelm.8b00111
|View full text |Cite
|
Sign up to set email alerts
|

BiFe1–xCrxO3 Ferroelectric Tunnel Junctions for Neuromorphic Systems

Abstract: We report on the fabrication of ferroelectric tunnel junctions of BiFe0.45Cr0.55O3 as a tunneling barrier, Nb-doped (111) SrTiO3 as a bottom electrode, and platinum as a top electrode. BiFeO3 is a generic multiferroic material with perspectives for multiferroic tunnel junctions, with chromium being introduced to shift and enhance the magnetic ordering from canted magnetization to ferrimagnetism. We deposit the ferroelectric films by radio frequency magnetron sputtering, an industry-compatible synthesis method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…The integration of multiferroic materials in the field of spintronics seems to be very promising not only for memories, for example magnetoelectric switching being very energy efficient, 60 but also for new scalable energy-efficient logic devices combining magnetoelectricity and spin-orbit coupling 61 . Broadly, multiferroics that have been proposed to date are either single-phase materials, which exhibit intriguing characteristics but allow for only limited degrees of freedom to engineer devices, or heterostructures coupling ferroelectric and ferromagnetic phases (e.g., via strain 62,63,64 ), which provide more design flexibility but may present their own integration challenges.…”
Section: Antiferromagnetic Spintronicsmentioning
confidence: 99%
“…The integration of multiferroic materials in the field of spintronics seems to be very promising not only for memories, for example magnetoelectric switching being very energy efficient, 60 but also for new scalable energy-efficient logic devices combining magnetoelectricity and spin-orbit coupling 61 . Broadly, multiferroics that have been proposed to date are either single-phase materials, which exhibit intriguing characteristics but allow for only limited degrees of freedom to engineer devices, or heterostructures coupling ferroelectric and ferromagnetic phases (e.g., via strain 62,63,64 ), which provide more design flexibility but may present their own integration challenges.…”
Section: Antiferromagnetic Spintronicsmentioning
confidence: 99%
“…[ 5 , 8 ] Among the various two‐terminal memristors, metal/ferroelectric/semiconductor (MFS) memristors utilizing Nb‐doped SrTiO 3 as a semiconducting substrate have exhibited high performance in resistive switching behaviors owing to the modulation of the ferroelectric barrier and depletion region in Nb‐doped SrTiO 3 semiconductors by ferroelectric polarization reversal. [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ] Progressive polarization reversal of the ferroelectric domain in MFS can improve the electrical modulation of the band profile between the high resistance state (HRS) and low resistance state (LRS), which can lead to high linearity/symmetry of the synaptic weight update when using a smart programming pulse. [ 9 , 10 , 11 , 12 , 13 , 16 ] However, parameter enhancement in weight update (linearity, symmetry, and variation) caused by interface engineering between the ferroelectric material and top electrode has not been addressed in MFS memristors reported earlier.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 , 10 , 11 , 12 , 13 , 16 ] However, parameter enhancement in weight update (linearity, symmetry, and variation) caused by interface engineering between the ferroelectric material and top electrode has not been addressed in MFS memristors reported earlier. [ 4 , 8 , 11 , 14 , 15 ] Moreover, high reading currents of the order of µA during synaptic operation pose a major challenge in implementing energy‐efficient large‐scale synaptic arrays based on MFS devices, although ultrafast synaptic operation with low energy consumption has been achieved. [ 2 , 3 , 4 , 8 , 11 , 14 , 15 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of cost issues and operation problems, these memories have not been very popular in commercial usage. , Beyond the destructive readout of the data from transistor-based ferroelectric memories, a variety of nondestructive readout methods have been introduced for these memories. One of them is atomic force microscopy (AFM), in which a probe sweeps the entire ferroelectric surface to read information. , In other works, high-speed reading has been successfully implemented by ferroelectric tunnel junctions, although the deposition of ultrathin films over large areas without defects is still a challenge. Recently, researchers have demonstrated that the conductivity of the domain walls in monocrystalline ferroelectrics can change based on the direction of the polarization. , However, the resistivity in this method remains challenging for the high-speed data readout …”
Section: Introductionmentioning
confidence: 99%